Metabolic Engineering Strategies of Industrial Hemp (Cannabis sativa L.): A Brief Review of the Advances and Challenges - Deguchi, Michihito; Kane, Shriya; Potlakayala, Shobha; George, Hannah; Proano, Renata; Sheri, Vijay; Curtis, Wayne R.; Rudrabhatla, Sairam (Frontiers in Plant Science, 2020)
Industrial hemp (Cannabis sativa L.) is a diploid (2n = 20), dioecious plant that is grown for fiber, seed, and oil. Recently, there has been a renewed interest in this crop because of its panoply of cannabinoids, terpenes, and other phenolic compounds. Specifically, hemp contains terpenophenolic compounds such as cannabidiol (CBD) and cannabigerol (CBG), which act on cannabinoid receptors and positively regulate various human metabolic, immunological, and physiological functions. CBD and CBG has an effect on the cytokine metabolism which has led to the examination of cannabinoids on the treatment of viral diseases including COVID-19. Based on genomic, transcriptomic and metabolomic studies, several synthetic pathways of hemp secondary metabolite production have been elucidated. Nevertheless, there are few reports on hemp metabolic engineering despite obvious impact on scientific and industrial sectors. In this article, recent status and current perspectives on hemp metabolic engineering are reviewed. Three distinct approaches to expedite phytochemical yield are discussed. Special emphasis has been placed on transgenic and transient gene delivery systems, which are critical for successful metabolic engineering of hemp. The advent of new tools in synthetic biology, particularly the CRISPR/Cas systems, enables environmentally friendly metabolic engineering to increase the production of desirable hemp phytochemicals while eliminating the psychoactive compounds such as tetrahydrocannabinol (THC).